DOI: 10.11606/t.8.2011.tde-25052012-094817
|View full text |Cite
|
Sign up to set email alerts
|

O nível de governo importa para a qualidade da política pública? O caso da educação fundamental no Brasil

Abstract: Esta tese beneficiou-se da colaboração, das sugestões e das críticas de muitas pessoas. Sob o risco de cometer desatenções imperdoáveis, deixando de fora algumas dessas pessoas, agradeço de forma especial aos professores Eduardo Marques e Matthew Taylor, do Departamento de Ciência Política da USP, presentes à banca de qualificação do projeto de pesquisa, pelos comentários e críticas que me permitiram corrigir aspectos importantes do desenho de pesquisa. Agradeço de forma especial, à orientação e a critica amig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(16 reference statements)
0
6
0
6
Order By: Relevance
“…12 More recent research has associated different municipal and state policies to student achievement, particularly the relationship between municipal spending in education and student achievement (do Amaral and Menezes-Filho 2008;Zoghbi et al 2009;Diniz 2012). Other studies have examined the impact of municipalization on Brazilian education 13 and found mixed results (Leme et al 2009;Ceneviva 2011;Becskeházy 2014). Using Prova Brasil data from 2005 to 2011, Soares and Alves (2013) compared student performance in state and municipal schools within each municipality by region.…”
Section: Educational Reforms and State Management Policiesmentioning
confidence: 99%
“…12 More recent research has associated different municipal and state policies to student achievement, particularly the relationship between municipal spending in education and student achievement (do Amaral and Menezes-Filho 2008;Zoghbi et al 2009;Diniz 2012). Other studies have examined the impact of municipalization on Brazilian education 13 and found mixed results (Leme et al 2009;Ceneviva 2011;Becskeházy 2014). Using Prova Brasil data from 2005 to 2011, Soares and Alves (2013) compared student performance in state and municipal schools within each municipality by region.…”
Section: Educational Reforms and State Management Policiesmentioning
confidence: 99%
“…In the education domain, Fundef led to the expansion of enrollment and reduction in intra-state per pupil spending inequality (Vazquez 2014). Nonetheless, findings have been ambivalent on the association between municipalization and educational outcomes -for instance, student performance at standardised tests (Leme, Paredes & Souza 2009;Ceneviva 2012). Taking Prova Brasil 6 scores as the dependent variable, Domingos, Silva and Souza (2013) found no statistical effect of municipality spending, while Amaral and Menezes-Filho (2008) observed a positive and significant effect only for the communities with top performance.…”
Section: Iii2 Decentralisation Of Education and Health Servicesmentioning
confidence: 99%
“…Since 1891 Catholicism is no longer the official religion, but there survives an implicit state recognition of Catholicism as the religious tradition of the majority in the official holiday in honor of Nossa Senhora Aparecida. Religious education is required as part of the public school curriculum but remains optional for students (Ceneviva 1995). Notwithstanding the liberal constitutional principles of the freedom of religion and the separation of church and state, such principles are sometimes undermined by legislative action or by the silence of the law itself on religion.7 In practice, the courts as well as the legislature may implicitly affirm the "customary" dominance of Catholicism in the interests of the collectivity as a whole.…”
Section: Church and State In Brazilian Historymentioning
confidence: 99%